Factors Underlying the Definition of Broad Money : An Examination of Recent U.S. Monetary Statistics and Practices of Other Countries - Lim, Ewe-Ghee (IMF Working Papers; Working Paper ;, 2003)
The paper examines the experiences of countries in defining monetary aggregates, particularly those countries that have undertaken substantial redefinitions. It finds that both the functional and empirical approaches are important; and that monetary definitions tend to be dynamic in nature, becoming prone to revisions whenever the current definition no longer satisfies both criteria. While countries may adhere to both approaches, monetary definitions may still vary across countries, reflecting specific institutional settings and the requirements of the empirical approach. This finding supports the approach in the IMF's Monetary and Financial Statistics Manual of not prescribing specific definitions of broad money.